2019
DOI: 10.1093/carcin/bgz103
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for malignant pleural mesothelioma: a meta-analysis

Abstract: Malignant pleural mesothelioma (MPM) is a rare but aggressive cancer, and early detection is associated with better survival. Mesothelin, fibulin-3 and osteopontin have been suggested as screening biomarkers. The study conducted a meta-analysis of the mean differences of mesothelin, osteopontin and fibulin-3 in blood and pleural samples. PubMed searches were conducted for studies that measured levels of mesothelin, osteopontin and fibulin-3 in participants with MPM compared with malignancy, benign lung disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 87 publications
1
25
0
2
Order By: Relevance
“…All available meta-analyses confirmed that SMRP is elevated in the serum of MM patients as compared to healthy individuals, patients with asbestos-related diseases, benign respiratory diseases or lung cancer. 12,14,16 Previous studies suggest that serum SMRP levels are the highest in epithelioid MM, which is consistent with our results. 12,14 Our present study also included patients with peritoneal MM who were rarely represented in other studies or meta-analyses that focused on pleural MM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All available meta-analyses confirmed that SMRP is elevated in the serum of MM patients as compared to healthy individuals, patients with asbestos-related diseases, benign respiratory diseases or lung cancer. 12,14,16 Previous studies suggest that serum SMRP levels are the highest in epithelioid MM, which is consistent with our results. 12,14 Our present study also included patients with peritoneal MM who were rarely represented in other studies or meta-analyses that focused on pleural MM.…”
Section: Discussionsupporting
confidence: 93%
“…Studies therefore suggest that SMRP measurement could be a potential screening tool for the detection of MM, but clinical use is still limited due to the probability of false positive and especially false negative results. 12,14,16 Some issues related to sensitivity may be associated with a difficult selection of an appropriate cutoff value and different studies found different optimal thresholds. 12,14,16 In our study, the standard cutoff of 1.5 nmol/l had 93% specificity and 59.3% sensitivity for distinguishing MM patients from other subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistically, significant mean differences have been found between MM patients and all the other comparison groups for mesothelin blood and pleural levels. It has been concluded that based on the findings, mesothelin levels seem to be significantly lower in all control groups compared with those with MM, suggesting a possible role of mesothelin as a screening biomarker for MM [30].…”
Section: Mesothelinmentioning
confidence: 87%
“…The meta-analysis of Gillezeau et al, which includes nine studies with fibulin-3 levels, also presented a statistically significant difference in both blood and pleural levels of fibulin-3 in MM patients compared with those of all other groups [30].…”
Section: Fibulinmentioning
confidence: 92%